Sosialisasi Strategi Pemasaran Bagi UMKM Kampung Keripik Desa Blerong - Ryan Arya Pramudya; Puji Setya Sunarka; Atika Mutiarachim (FKIP, Universitas Palangka Raya, 2025)
Belerong Village is one of the villages in Guntur Demak sub-district which has a group of MSMEs that produce various kinds of processed chips, using the community's agricultural products. Many challenges faced by MSMEs in developing their business include marketing, for this reason the socialization activities carried out are focused on how marketing processes and marketing strategies can be carried out so that the results from the chips village can be distributed smoothly so as to make the development of MSMEs more significant, followed by economic development among group members in particular and Blerong sub-district residents in general.